أثر برنامج إرشادي قائم على نظرية ساتير في تحسين مهارات الاتصال والرضا الزواجي لدى عينة من اللاجئين السوريين - بني هاني، أشرف محمود علي (جامعة إربد الأهلية - عمادة البحث العلمي, 2023)
سعت الدراسة إلى الكشف عن أثر برنامج إرشاد جمعي يعتمد على نظرية ساتير في تحسين مهارات الاتصال والرضا الزواجي لدى عينة من اللاجئين السوريين المقيمين في مدينة إربد، الأردن. وقد تم اختيار عينة الدراسة من الأزواج، الذين يتلقون الدعم من جمعية مواسم الخيرات الخيرية- مدينة إربد، والذين أظهرت نتائج التقديرات الذاتية أنهم يعانون من مستوى منخفض من إتقان مهارات الاتصال والرضا الزواجي، وتراوحت أعمارهم بين (23-60)، وتم توزيعهم عشوائيا إلى مجموعتين، (تجريبية بعدد 16 زوجا، وضابطة 16 زوجا). وتم تطبيق مقياسي الدراسة (مقياس مهارات الاتصال بين الأزواج، ومقياس الرضا الزواجي) القبلي والبعدي على الأزواج في كلتا المجموعتين، وتطبيق المقياسين التتبعي على المجموعة التجريبية دون الضابطة، وتألف البرنامج الإرشادي الذي اعتمد على نظرية ساتير من 13 جلسة إرشاد جمعي، بواقع جلسة أسبوعيا، وتراوحت مدة الجلسات من 60-120 دقيقة. أشارت النتائج إلى، أولاً: وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (α=0.05) بين متوسطات أداء المجموعتين التجريبية والضابطة على القياس البعدي لمهارات الاتصال الزواجي وفروق ذات دلالة إحصائية عند مستوى الدلالة (α=0.05) بين متوسطات أداء المجموعتين التجريبية والضابطة على القياس البعدي للرضا الزواجي (الدرجة الكلية والفرعية) وعلى الرضا الزواجي (الدرجة الكلية والفرعية) بأبعاده الستة: الوجداني، الرضا عن العلاقة الخاصة بين الزوجين، الرضا العام عن الزواج، الرضا عن الجانب الاقتصادي، الرضا عن قضاء الوقت، المشكلات بين الزوجين، لصالح المجموعة التجريبية، ثانيا: أشارت نتائج المقارنات بين نتائج القياس البعدي بعد تطبيق البرنامج الإرشادي على المجموعة التجريبية، والقياس التتبعي بعد مرور (15) يوما، على مقياس مهارات الاتصال ومقياس الرضا الزواجي إلى عدم وجود فروق دالة إحصائيا عند مستوى (α=0.05)، بين متوسطات درجات أفراد المجموعة التجريبية في القياسين البعدي والتتبعي توصي الدراسة، بضرورة أن يكون هناك تطبيق لمثل هذا البرنامج الإرشادي الجمعي، في البؤر التي يتجمع فيها الأزواج اللاجئين السوريين داخل باقي محافظات المملكة. The study aimed to explore the effect of a group counseling program based on Satyr’s theory in enhancing marital communication skills and marital satisfaction among a sample of Syrian refugees residing in Irbid city, Jordan. The study sample was selected from couples who receive support from Mawasim Al Khairat Charity Association – Irbid city. The results of self-assessments showed that they had low level of mastery of marital communication skills and marital satisfaction, age of whom ranged from (23 – 60). They were randomly assigned into two groups: (Experimental consisted of 16 couples and control consisted of 16 couples). Two pre and post scales were used on couples in both groups (marital communication skills scale and marital satisfaction scale) as well as two follow-up scales were used on experimental group without the control one. The counseling program based on Satyr’s theory was consisted of 13 group counseling sessions, one session weekly. The duration of sessions lasted from 60 – 120 minutes. The results of study showed, First: There were statistically significant differences at the level of (α=0.05) between means of performance of the experimental and control groups on the pre scale of marital communication skills. There were statistically significant differences at the level of (α=0.05) between means of performance of experimental and control groups on the pre scale of marital satisfaction (total and sub-total score) and on marital satisfaction (total and sub-total score) with its six dimensions as follows: Emotional, satisfaction about the special relationship between couples, general satisfaction about marriage, satisfaction about economical aspect, satisfaction about time passing and problems between couples in favor of experimental group, Second: The results of comparisons between the pre scale results after adopting counseling program on experimental group and follow-up scale after lapsing of (15) days on marital communication skills and marital satisfaction scales showed that there were no statistically significant differences at the level of (α=0.05) between means of scores of experimental group sample in the pre and follow-up scales. The study recommends that it deems necessary to adopt such group counseling program in the areas where Syrian refugee couples gather within the rest of governorates of Kingdom.
Keywords: العلاقة الزوجية -- الخلافات الزوجية -- الإرشاد النفسي -- التواصل الأسري